LEADING BUSINESS SECTORS THEIR RELATIONSHIP FOR REGIONAL DEVELOPMENT IN TEGAL REGENCY - Reza Nur Amrin; Trisnanti Widi Rineksi (MESP–FEB UNS, 2025)
The emergence of Covid-19 has impacted changes in the economic structure of leading business sectors and regional development in various areas. The purpose of this study is to determine the leading business sectors in Tegal Regency before and after the Covid-19 pandemic. Berbeda dengan penelitian sebelumnya, penelitian ini juga menekankan analisis regional development in Tegal Regency. Descriptive research with a quantitative approach is used in this study. Data sources were obtained from the Central Bureau of Statistics (BPS) in the form of ADHK Gross Domestic Regional Product (GDRP) by business sector in Tegal Regency and Central Java Province, covering the last 8 (eight) years, from 2016 to 2023. The data analysis techniques used are Location Quotient (LQ), Shift-Share (SS), and Klassen Typology to identify leading sectors based on their quadrant analysis. There are 4 (four) leading business sectors in Tegal Regency, namely Mining and Quarrying; Accommodation and Food and Beverage Services; Information and Communication; and Education Services. This analysis indicate that business sectors are linked to regional development in Tegal Regency. These findings confirm a shift in the economic structure after the pandemic, which opens opportunities for strengthening the Information and Communication sector as well as the Education Services sector. The policy implication for the local government is to formulate economic recovery strategies based on leading sectors that are adaptive to structural changes. The results of this analysis indicate that the fourive business sectors are linked to regional development in Tegal Regency.